The Effect of Green Phoskko and EM4 Activators on Making Compost Fertilizer from a Mixture of Pineapple Peel Waste and Rabbit Feces Using the Windrow Method - Meisya Royani; Natalina (Ambidextrous Journal of Innovation Efficiency and Technology in Organization, 2025)
Abstract: Composting is an environmentally friendly method of processing organic waste that can produce high-value organic fertilizer. Organic wastes such as pineapple peels and rabbit manure have potential as compost raw materials due to their high organic carbon and nitrogen content. In this study, a ratio of pineapple peel and rabbit manure of 1:1 (wet weight) was used to obtain an appropriate initial C/N ratio. However, an unbalanced C/N ratio requires special treatment to optimize the decomposition process. The purpose of this study was to determine the effect of using the windrow method with the addition of Effective Microorganisms 4 (EM4) and Green Phoskko activators on C-organic content, total nitrogen, and the resulting compost C/N ratio. The research was conducted using an experimental method with a complete randomized design (CRD) consisting of three treatments, namely: no activator (control), addition of EM4, and addition of Green Phoskko. The compost material was arranged in the form of an elongated pile (windrow), turned periodically, and measured temperature, pH, C-organic content, total nitrogen, and C/N ratio every week for 28 days (4 weeks) of the composting process. Laboratory analysis was conducted at Lampung State Polytechnic Laboratory. The results showed that treatment with EM4 produced C-organic content of 17.26%, total nitrogen of 1.63%, and C/N ratio of 10.59, while Green Phoskko produced C-organic content of 16.22%, total nitrogen of 1.45%, and C/N ratio of 11.18, and the control produced C-organic content of 15.64%, total nitrogen of 1.30%, and C/N ratio of 12.03. the compost treated with EM4 and Green Phoskko has met the standards of good compost quality.